Will European agriculture be resilient? Assessment of the share and economic resilience levels of the future European farmer profiles: Evidence from Lithuania - Artiom Volkov; Mangirdas Morkūnas; Agnė Žičkienė; Elzė Rudienė (Agricultural and Food Economics)
Abstract The present paper is the first scientific investigation of the future European farmer profiles. An expert interview combined with sophisticated multi-criteria decision-making techniques were employed as main research tools. Lithuania served as an empirical basis for the research. The dynamics of the development of the share of future European farmer profiles in 2023 and 2040 is assessed. The resilience index for the calculation of the agricultural economic resilience level for the each of the future European farmer profiles is created. The most resilient appear to be social care and controlled environment farmer profiles, while intensive, regenerative and corporate farmer profiles tend to show the lowest level of agricultural economic resilience. This fact poses a risk to Lithuanian agriculture, as these, least resilient, farmer profiles dominate the agricultural sector. Thus, some steering actions toward increasing the share of the more resilient future European farmer profiles in Lithuania are required.